Prognostic value of ventricular longitudinal strain in patients undergoing transcatheter aortic valve replacement: A systematic review and meta-analysis - Xiao, Yangjie; Bi, Wenjing; Qiao, Wei; Wang, Xin; Li, Ying; Ren, Weidong (Frontiers in Cardiovascular Medicine, 2022)
Introduction Strain obtained by speckle tracking echocardiography (STE) can detect subclinical myocardial impairment due to myocardial fibrosis (MF) and is considered a prognostic marker. Aortic stenosis (AS) is not only a valve disease, but also a cardiomyopathy characterized by MF. The purpose of this study was to systematically review and analyze ventricular strain as a predictor of adverse outcomes in patients with AS undergoing transcatheter aortic valve replacement (TAVR). Methods PubMed, Embase, and the Cochrane library were searched for studies that investigated the prognostic value of impaired ventricular strain on patients with AS undergoing TAVR with all-cause mortality (ACM) and major adverse cardiovascular events (MACE). Pooled odds ratios (ORs), hazard ratios (HRs), and 95% confidence intervals (CIs) were calculated to assess the role of left (LVLS) and right (RVLS) ventricular longitudinal strain in the prognostic prediction of patients with AS undergoing TAVR. Sensitivity and subgroup analysis was performed to assess heterogeneity. Results Twelve studies were retrieved from 571 citations for analysis. In total, 1,489 patients with a mean age of 82 years and follow-up periods varying between 1 year and 8.5 years were included. Meta-analysis showed the impaired LVLS from eight studies was associated with an increased risk for combined ACM and MACE (OR: 1.08, 95% CI: 1–1.16; p = 0.037), and ACM alone (HR: 1.08, 95% CI: 1.01–1.16; p = 0.032). Impaired RVLS from four studies was associated with an increased risk of combined ACM and MACE (OR: 1.08, 95% CI: 1.02–1.14; p < 0.01), and ACM alone (HR: 1.07, 95% CI: 1.02–1.12; p < 0.01). Conclusions This meta-analysis demonstrated that ventricular strain, including LVLS and RVLS, had a substantial prognostic value in ACM or combined ACM and MACE, which could be used as a valid marker for risk stratification in patients with AS undergoing TAVR.